The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3163/1536-5050.97.4.008
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Web 2.0 technologies using Web 2.0 technologies

Abstract: Learning 2.0-style courses, though demanding time and self-motivation from participants, can increase knowledge of Web 2.0 tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…In this study, participants reported that the lessons on blogs, wikis, and social bookmarking were the most useful. Furthermore, although the study showed that participants learned the most new information about the mash-up technologies, they did not report it would be very useful to them (Rethlefser, Piorun, & Prince, 2009).…”
Section: Social Bookmarkingmentioning
confidence: 91%
“…In this study, participants reported that the lessons on blogs, wikis, and social bookmarking were the most useful. Furthermore, although the study showed that participants learned the most new information about the mash-up technologies, they did not report it would be very useful to them (Rethlefser, Piorun, & Prince, 2009).…”
Section: Social Bookmarkingmentioning
confidence: 91%
“…A educação permanente por meio das ferramentas da TIC, por vezes reduz os custos, é rápida, eficaz e democratiza a qualificação entre os trabalhadores e profissionais da saúde. 3,7,10,18,22,25,27,44 Dicotomicamente ao debate da relação uso da máquina e humanização, estudos sinalizam que a tecnologia, quando bem utilizada pode favorecer a humanização da assistência, pois pode contribuir para qualificação da assistência, promover a segurança dos usuários e aumentar o tempo disponível para planejar e assistir. 18 Ainda, as TIC favorecem a globalização do conhecimento, a ampla divulgação do mesmo e o acesso à realidade e a pesquisas que vem sendo realizadas em todo o mundo.…”
Section: Benefícios Das Tecnologias De Informáticaunclassified
“…The literature is replete with articles on librarians teaching the fundamentals of using social media tools to their staffs and colleagues. [1][2][3][4][5][6][7] The most prominent teaching model in the library world is the so-called ''Learning 2.0'' method, created by Helene Blowers for the Charlotte Mecklenburg Library. 1 The Learning 2.0 method is based on the concept of active learning; participants have to actively use blogs, wikis, and other Web 2.0 or social media tools to accomplish course objectives.…”
Section: Introductionmentioning
confidence: 99%
“…1 The Learning 2.0 method is based on the concept of active learning; participants have to actively use blogs, wikis, and other Web 2.0 or social media tools to accomplish course objectives. 6 Though libraries were among the first major groups of Web 2.0=social media adoption, the clear utility and importance of these technologies quickly made them hot topics in other industries and arenas, including education and health care. In health care, particularly, social media is both lauded as the new way to engage patients, donors, staff, and students and decried for its potential for violation and harm.…”
Section: Introductionmentioning
confidence: 99%